(untitled) (Research, Society and Development, 2022)
This article started from the experience of Supervised Internship II, being a mandatory activity of the distance education course (DEC) of chemistry degree, university of Uberaba (UNIUBE) pole Belém-Pará. The writing derives from a practical and reflective exercise of supervised internship in the second year of high school classes of the Escola Estadual de Ensino Fundamental e Médio Dom Pedro II, located in the Brazilian Amazon, in the city of Belém in the State of Pará. The practice of the internship was performed in high school classes, being made the observations of the classes, collaboration through monitoring and teaching in the classroom, being all activities duly accompanied by the internship supervisor. The internship conferred a total hourly load of 240 hours and aimed to analyze the experience of the internship, more precisely, the observation of the neighborhood where the school is located, the observation of the school and its history, knowing the spaces, materials and pedagogical resources, making reflections and analyses on the political pedagogical project (PPP), in addition to observations and analyses of chemistry teaching and put an end to monitoring and teaching for high school classes. The supervised internship enabled the union between theory and practice in the classroom, assisting in the construction of the teacher identity with commitment, discipline and planning for more effective actions.